CREATIVE APPROACHES TO THE MANAGEMENT OF THE DEVELOPMENT OF THE TOURIST INDUSTRY IN THE CONDITIONS OF A PANDEMIC CRISIS - Svydruk, Irena (Економічний дискурс, 2021)
Introduction. The success of the creative development of the tourism industry in a pandemic lockdown and in the post-quarantine period is closely related to the quality of a number of factors that shape the level of creative activity of its subjects and provide competitive advantages. Adequate choice and scientific substantiation of strategic alternatives for the development of the tourism industry highlights the need for a targeted study of the parameters of its creative renewal. Methods. Methods of scientific abstraction, analysis and synthesis are used, technologies of structuring and systematization are applied during construction of logical-structural decomposition of creativity of tourist destinations and structural model of management of tourist cluster. The SWOT analysis was used to evaluate strategic alternatives for the development of tourism entities. Results. The generalization of research on the peculiarities of the functioning of the tourism sector in the context of the socio-economic crisis caused by pandemic constraints, suggests that the restoration of effective business entities should be managed, targeted action of all participants. At the same time, ensuring the efficiency of the tourism industry requires the implementation of creative technologies in management algorithms at all stages of overcoming the crisis. Qualitative goals of post-pandemic recovery of the industry can be generalized in the form of two main directions: 1) creation of creative tourist offer (including tourist experience and offer of original tourist product) on the basis of high-quality entertainment industry, introduction of European market trends, with emphasis on authentic values ; 2) building a clear identity of domestic tourism enterprises, which would synergistically connect micro-destinations, emphasizing the creative benefits in the minds of potential tourists. Discussion. Further research on the possibilities of creative management to overcome the crisis in the tourism industry should cover the problems of creating unique tourism products based on authentic values, reducing the seasonality of domestic resorts, modernization of tourism infrastructure and integration of tourist inactive regions in creative projects.